On the cusp of the canon : English children’s literature in the first half of the 19th century - Williams, Sandra (Array, 2020)
This period, the first half of the 19th century, stands on the cusp of the first Golden Age of English children’s literature. While publications from the mid-1800s onwards, such as Alice’s Adventures in Wonderland, The Secret Garden and The Wind in the Willows, have become part of the cultural landscape, those from the first half of the 19th century are largely unfamiliar and forgotten. If read at all, they are studied by academics rather than read by children. Publications at that time reveal the tensions between the perceived need for improving, moralising books and those that might give pleasure to the reader. It will be argued in this article that amongst the more didactic works, there are indicators of what was to follow. Attention is drawn to chapbooks for children and to a number of titles which have enjoyed a degree of longevity.